Maturation toward neuronal tissue in a Ewing sarcoma of bone after chemotherapy. Issue 1 (December 2016) - Salet, Maria; Vogels, Rob; Brons, Paul; Schreuder, Bart; Flucke, Uta
Abstract Background Ewing sarcoma is the second most common bone tumor, occurring mainly in children and young adults. It shows a typical primitive, small round cell morphology and a characteristic fusion oncogene involvingEWSR1 and members of the ETS family in most of the cases. Neuronal maturation after chemotherapy is a rare phenomenon and we herein describe such an exceptional case. Case presentation An 8-year old boy was diagnosed with a Ewing sarcoma in the left femur. On biopsy the morphology was typical and there was anEWSR1-FLI1 gene fusion. He underwent neo-adjuvant chemotherapy and resection of the tumor. On microscopic evaluation, part of the tumor showed ganglioneuroblastoma-like differentiation with expression of neuronal markers. The continued presence ofEWSR1 rearrangement in both the blue round cell component and the ganglioneuroblastoma-like component was shown by FISH analysis. Conclusions In conclusion, this case describes the possibility of a Ewing sarcoma to differentiate into a ganglioneuroblastoma-like lesion after neo-adjuvant chemotherapy treatment; the prognostic value of this phenomenon remains questionable.